Pengaruh model pembelajaran kooperatif tipe stad terhadap hasil belajar siswa pada materi atom dan partikel penyusunnya - Jamilah Jamilah; Rody Putra Sartika; Maria Ulfah (IKIP PGRI Pontianak, 2021)
This study aimed to determine: 1) the differences in student learning outcomes taught used the STAD cooperative learning model used conventional learning models on atomic material and the constituent particles, 2) the magnitude of the influence of the STAD cooperative learning model on student learning outcomes on atomic and particle material constituent. The form of this research was true experimental design with posttest only control design. The sample selection technique was carried out by simple random sampling. The data collection tool was used a learning outcome test. The results of data analysis through the U-Mann Whitney test on the posttest value obtained a Sig value of 0.000 which indicates that there were differences in learning outcomes between students who were taught used the STAD type cooperative learning model and students taught used conventional methods on atomic material and the constituent particles. Learning used the STAD cooperative learning model on atomic material and its constituent particles at SMP Negeri 9 Pontianak class IX has an effect of 37.06% on student learning outcomes.